2003
DOI: 10.1016/j.icarus.2003.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Photometric survey of the irregular satellites

Abstract: We present BVRI colors of 13 Jovian and 8 Saturnian irregular satellites obtained with the 2.56m Nordic Optical Telescope on La Palma, the 6.5m Magellan Baade Telescope on La Campanas, and the 6m MMT on Mt. Hopkins. The observations were performed between December 2001 to March 2002. Nearly all of the known irregular satellites can be divided into two distinct classes based on their colors. One, the grey color class, has the similar colors to the C-type asteroid, and the other, the light red color class, has c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
96
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 40 publications
20
96
1
Order By: Relevance
“…Spectroscopic studies show a large diversity of colors (ranging from gray to very red ) among observed irregular satellites of four outer planets (Cruikshank 1980;Degewij et al 1980;Dumas et al 1998;Brown 2000;Sykes et al 2000;Grav et al 2003Porco et al 2005). This diversity would be difficult to understand if irregular satellites were captured from a local and dynamically cold population of planetesimals at the planet's heliocentric position, because in such a case the colors should be homogeneous (reflecting the local composition) and there should exist a clear color gradient of irregular satellites with heliocentric distance (i.e., from Jupiter to Neptune).…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic studies show a large diversity of colors (ranging from gray to very red ) among observed irregular satellites of four outer planets (Cruikshank 1980;Degewij et al 1980;Dumas et al 1998;Brown 2000;Sykes et al 2000;Grav et al 2003Porco et al 2005). This diversity would be difficult to understand if irregular satellites were captured from a local and dynamically cold population of planetesimals at the planet's heliocentric position, because in such a case the colors should be homogeneous (reflecting the local composition) and there should exist a clear color gradient of irregular satellites with heliocentric distance (i.e., from Jupiter to Neptune).…”
Section: Introductionmentioning
confidence: 99%
“…All of this seems to support the idea of a collisional scenario. However, the existence of a dynamical grouping (Kavelaars et al 2004;Sheppard et al 2005) is still debated on the light of the colour determination of Grav et al (2004b). Regrettably, there seems to be a lack of consistency between B − V and V − R colours of different authors for Sycorax and Caliban (Maris et al 2001;Rettig et al 2001;Romon et al 2001;Grav et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Photometry of the jovian and saturnian irregular satellites shows that most satellite clusters have homogeneous colours, thus intimating that irregulars are collisional fragments of larger progenitors 28,29 . Following the discovery of type-II high-temperature superconductors in 1986 (refs 1, 2), work has proceeded to develop these materials for power applications.…”
mentioning
confidence: 99%